바이오매스 연료의 연소 특성 실험 - 김학덕(Hakdeok Kim); 김영대(Youngdae Kim); 송주헌(Juhun Song) (한국수소 및 신에너지학회 논문집, 2018)
There have been many studies of combustion in the circulating fluidized bed. However, little study is available for combustion of wood pellet together fed with wood chip. The mixed ratio of two fuels is an useful information when thermal power company would receive the Renewable Energy Portfolio Standard (RPS) from government. In this study, the combustion behavior and kinetics of such biomass fuels are evaluated using fluidized bed reactor and thermogravimetric analyzers. The mixing ratio of wood chip relative to wood pellet was varied at different temperatures. The results show that a combustion reactivity changed significantly at the wood chip mixing ratio of 40%, particularly at low temperature condition.